An experimental study of optimal regenerator configurations for LDAC systems - Ooi, Wen Song (2015)
Singapore has been an active participant in finding effective and efficient solutions for the energy crisis and environmental issues. Being a country that experiences high daily temperatures and high levels of humidity, finding an energy and environmentally-friendly solution for the air-conditioning system is an imperative. The Liquid Desiccant Air Conditioning (LDAC) system is a viable option that has been studied for many years. It can effectively reduce latent load off conventional vapour compression air-conditioning systems while still delivering air that satisfies indoor thermal comfort standards. The present work aims to study the performance of one of such LDAC systems, specifically the regenerator and its optimal configuration. The regenerator uses a novel Vacuum-Multi-Effect-Membrane-Distillation (V-MEMD) technology to separate water from weak desiccant solutions. Experiments revolving four different configurations were conducted: Conventional Four-Stage, Conventional Two-Stage, Hybrid 1S-3L and Hybrid 2S-4L. The former two configurations were deemed to be unsuitable due to their inability to perform above feed concentrations of 22%. Ultimately, it was concluded that the Hybrid 1S-3L configuration performed the best in terms of concentration increment and performance ratio. It was hence selected to be used with the overall LDAC system for further performance studies.